(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article is devoted to the study of legal mechanisms for the protection of trade secrets within the framework of non-contractual (tort) relations under the legislation of the Republic of Uzbekistan. Based on the Law of the Republic of Uzbekistan “On Trade Secrets,” the Civil Code, the Criminal Code, and the Code on Administrative Responsibility, the article analyzes the grounds and procedures for holding violators liable, examines the judicial practice of economic and civil courts, identifies systemic gaps in legal regulation, and proposes directions for their elimination. Particular attention is paid to issues of proof, the correlation between tort and condiction claims, as well as the international legal dimension of the problem in the context of Uzbekistan’s membership in the WTO.